THE EFFECT OF COOPERATIVE LEARNING MODEL GROUP INVESTIGATION (GI) TYPE TO CONCEPTUAL KNOWLEDGE STUDENT’S IN TOPIC OPTIC GEOMETRY GRADE X SMAN 1 PERBAUNGAN ACADEMIC YEAR 2014/2015 - Elmina S. Panjaitan; Sahyar . (INPAFI (Inovasi Pembelajaran Fisika), 2016)
ABSTRACT The objective of this research was to analysis the Cooperative Learning Model to student’s learning outcomes by using cooperative learning model Group Investigation type to conceptual knowledge. In experimental class used cooperative learning model GI type while in the control class used conventional learning model. In each class used pre-test and post-test, after that was done the data analysis technique like average value, standard deviation, normality test, homogeneity test, hypothesis test. The results were showed the increasing of student learning outcomes that used model GI type in conceptual knowledge with post-test value was higher 78.37 in the class experiment than 69.68 in the control class, the active of students and then the conceptual knowledge when the model of GI type were happened. From the research get the conclusion that there was effect of Cooperative learning model Group Investigation type to conceptual knowledge students. Key word : Cooperative, Group Investigation, Conceptual Knowledge, Student’s Learning Outcome.